THE CONCEPT OF SUFFERING IN CLASSICAL SAMKHYA - Kenney, J. Frank (Journal of Dharma, 1977)
While the concept of suffering is undoubtedly central to Classical Samkhya serious questions remain regarding its nature and function.' One reason is the surprising lack of textual refer- ences. For example, the Siimkhyakiirika contains only two re- ferences to dubleba, the basic term for "suffering" in the Samkhya tradition. The first reference (Karika 1) refers to the torment (abbighiita) of a three-fold suffering (dubkba) which is said to cause the desire for release, while the second reference (Karika 55) claims that purusba somehow attains (prdpnoti) phenomenal suffering. Such references, however, raise more questions than they solve. What is the torment (abhighato) of suffering referred to in Kdrika I? What is the three-fold suffering and what is its relationship to abbigbata? Finally, how can purusba be affected by phenomenal suffering when it is never bound and never re- leased (Kdrilea 62)? I shall first offer a general overview of Samkhya metaphysics with particular attention to the concept of suffering as "ignorance" (avidya). I shall then propose the follow- ing in response to the above questions: (1) suffering (dubkha) in the Samkhyakarika is no ordinary suffering but rather a special suffering which results from a unique experience (abbigbata), namely, the individual's awareness or consciousness of the limita- tion, inadequacy and emptiness of his human condition; (2) this experience is all-inclusive, the product of a profound disillusion- ment on every level of phenomenal reality: individual, social and cosmic; and (3) this experience motivates the individual to prac- tise Samkhya yoga which, in turn, culminates in the permanent en stasis of purusba understood as a state of consciousness in which the individual no longer experiences the bondage of fini- tude,